2017
DOI: 10.1016/j.electstud.2016.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Door-to-door canvassing in the European elections: Evidence from a Swedish field experiment

Abstract: In this paper I report the results from a door-to-door canvassing experiment conducted in Sweden during the 2014 European elections. The canvassing was performed by members of the Social Democratic Party and the experiment closely resembles the partisan nature of most mobilizing campaigns in Europe. The paper is one of the first to provide causal evidence for the mobilizing effectiveness of canvassing outside the United States. Living in a household that was visited by canvassers increases the probability of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…It should, however, be noted that most of these field experiments have been conducted in the US. Experiments with door-to-door canvassing in Europe have had little or no effect (Bhatti et al 2016;Nyman 2017). Other experiments have been more in line with results from the US.…”
Section: Introductionsupporting
confidence: 67%
“…It should, however, be noted that most of these field experiments have been conducted in the US. Experiments with door-to-door canvassing in Europe have had little or no effect (Bhatti et al 2016;Nyman 2017). Other experiments have been more in line with results from the US.…”
Section: Introductionsupporting
confidence: 67%
“…11 John and Brannan 2008. 12 Cantoni and Pons 2016;Foos and John 2016;Nyman 2014;Pons and Liegey 2016;Ramiro, Morales, and Jiménez-Buedo 2012. 13 Karp, Banducci, andBowler 2007. 14 Ramiro, Morales, andJiménez-Buedo 2012.…”
mentioning
confidence: 99%
“…In the United Kingdom, beyond a handful (Foos and John 2016;Foos and de Rooij 2017), existing GOTV experiments have focused on non-partisan interventions (e.g., John and Brannan 2008;Fieldhouse et al 2013). An experiment in Sweden found that party canvassing increases turnout by 3.6 percentage points (Nyman 2017), while Cantoni and Pons (2016) find an effect size of around 2 percentage points in France. Meanwhile, experiments that randomize party contact at the aggregate level often show null effects (Ramiro, Morales and Jiménez-Buedo 2012;Pons and Liegey 2018;Pons 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, it would be wise to treat this effect as a potential outlier. Indeed, given the size, and with so few other European experiments testing the impact of party leaflets (studies so far have tested canvassing, for example, Ramiro, Morales and Jiménez-Buedo 2012; Pons and Liegey 2018;Bhatti et al 2016;Cantoni and Pons 2016;Pons 2018;Nyman 2017, or phone calls, e.g., Foos and de Rooij 2017), replication and further research into the effects of different designs and types of leaflets is merited.…”
mentioning
confidence: 99%